IMP3 Is Strongly Expressed in Malignant Phyllodes Tumors of the Breast: An Immunohistochemical Study. (February 2016) - Bellezza, Guido; Prosperi, Enrico; Del Sordo, Rachele; Colella, Renato; Rulli, Antonio; Sidoni, Angelo
Background . Phyllodes tumors (PTs) of the breast are rare biphasic neoplasms and are classified as benign, borderline, or malignant. Many biological markers have been studied to discriminate between different grades of PTs. IMP3 is a member of the insulin-like growth factor II mRNA binding protein (IMP) family and is expressed in developing tissues during embryogenesis, whereas in adult tissues it is found only at low or undetectable levels. IMP3 is considered a marker of biological aggressiveness in many cancers, including breast and lung. The aim of this study was to evaluate the immunohistochemical expression of IMP3 in a series of PTs and to determine its association with histological grade and clinical outcome. Materials and Methods . We reviewed retrospectively 62 cases of PTs including their recurrences and 20 cases of fibroadenoma. PTs have been classified as benign in 40 cases, borderline in 13 cases, and malignant in 9 cases. Results . There were significant differences in IMP3 expression: in malignant PTs IMP3 expression was higher (56% of cases) than in borderline (15%) and benign cases (5%), ( P = .001). Fibroadenoma showed no expression for IMP3. IMP3 expression was different in cases with recurrence than cases without recurrence. Furthermore, 3 of the recurrences had a higher histological grade with a positive IMP3 expression compared with the primary tumor. Conclusions . This is the first study evaluating the IMP3 immunohistochemical expression in PTs. Its expression correlates with histological grade and could be used in the differential diagnosis of fibroepithelial tumors and in predicting a more aggressive behavior.